Does Religion Promote Violence? - Augustine Perumalil (Satya Nilayam: Chennai Journal for Intercultural Philosophy 6 (2004), 102-127, 2004)
Observing that violence in the name of religion has a long history, the article enquires into the relationship between religion and violence. The enquiry begins with a critical examination of two views of religion-inspired violence which are popular in certain circles - the view that it is in the very nature of religion to generate violence; and that the cause of religious violence is the presence of male pronouns and violent images in religious discourse - and finds them inadequate accounts of religion-inspired violence. The enquiry further looks into the various factors, both internal and external, that make religion violent and comes to the conclusion that there is no purely religious violence. Much of the violence attributed to religion is in fact caused by deeper social, economic and political conflicts arising from the avarice of certain sections of society for dominion, and from a sense (actual or imaginary) of deprivation, injury, injustice and insecurity of the masses. Consequently, the writer argues, any attempt to grapple with violence done in the name of religion will have to first address these aspects of social life and seek a separation of nationhood from religious affiliation, of national ethos from religious identity.